(NwELIKOBRITANIQ I aRMQNSKIJ WOPROS(B: (90-(NE GODY (BXIX (NWEKA(B) /s - d; d ((NeREWAN (B:s (NaJASTAN(B,s, 1990)
(NrEZ(B.: (NANGL(B.s
(NbIBLIOGR(B. (NW PODSTRO^(B. (NPRIME^(B., (NSTR(B. 214-230.s
(NpRIME^(B.: (NS(B.200-213. - (NuKAZ(B. (NIMEN(B., (NSTR(B. 230-235.s
Keywords: (NiSTORIQ ARMQNSKOGO NARODAs; (NwELIKOBRITANIQs -- (NwNE[NQQ POLITIKAs; 9; (NzAPADNAQ aRMENIQs -- 90-(NE GG(B. XIX (NW(B.s